Joan Hardman interviewed by Christine Brown for the Australia 1938 oral history project - Hardman, Joan, 1918-; Brown, Christine; Australia 1788-1988: A Bicentennial History; Australia 1938 Oral History Project (1982)
Hardman speaks of her family background; family immigrating from England in 1918; family life and lifestyle in Australia; childhood memories growing up in Swanbourne W.A.; employment experiences and conditions working in a clothing factory in Perth; lifestyle when working; memories of the 1930s.
Working duplicate unavailable.
Recording is accompanied by photographs.
Recorded by the Australia 1938 Oral History Project as research for the book Australians 1938 from the series Australians, a historical library.
Digital master available
Partial transcript (4 p.)
Keywords: Hardman, Joan, -- 1918- -- Interviews; Women -- Western Australia -- Social conditions; Clothing factories -- Western Australia; Swanbourne (W.A.) -- Social conditions